Fillers for the improvement in acne scars - Wollina U; Goldman A (Dove Medical Press, 2015)
Uwe Wollina,1 Alberto Goldman2 1Department of Dermatology and Allergology, Academic Teaching Hospital, Dresden-Friedrichstadt, Dresden, Germany; 2Clinica Goldman, Porto Alegre, Rio Grande do Sul, Brazil Abstract: Acne is a common inflammatory disease. Scarring is an unwanted end point of acne. Both atrophic and hypertrophic scar types occur. Soft-tissue augmentation aims to improve atrophic scars. In this review, we will focus on the use of dermal fillers for acne scar improvement. Therefore, various filler types are characterized, and available data on their use in acne scar improvement are analyzed. Keywords: acne, scars, dermal fillers, injection, extracellular matrix